The Effect of Financial Literacy, Capital Variation, Risk Tolerance, and Herding Behavior on Investment Intention - Rifqi Nisa Rahmaddani Pangesti; Tyas Danarti Hascaryani (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2026)
Despite the fact that information and investment facilities are becoming more widely available, the phenomenon of low public participation in investing serves as the basis for this study's analysis of the relationship between financial literacy, capital variation, risk tolerance, and herding behavior and interest in investing. This research uses a quantitative approach and data obtained by distributing questionnaires online to 100 eligible respondents. The analysis technique to answer the problem and hypothesis with the path coefficient test in the SmartPLS program. The results showed that financial literacy, risk tolerance, and herding behavior have a positive and significant effect on investment interest A statistically significant negative effect is seen in the variation of capital. This research suggests that people's interest in investing is significantly influenced by their attitude toward risk, increased financial literacy, and convenience of choosing an investment amount. The implication of this study is the importance of financial education and individualized approach in encouraging public participation in investment.